Endotoxin-free purification of recombinant membrane scaffold protein expressed in Escherichia coli. (March 2018) - Moon, Seokoh; Kong, Byoungjae; Jung, Young-Hun; Kim, Yuna; Yu, Seokhyeon; Park, Joon-bum; Shin, Jonghyeok; Kweon, Dae-Hyuk
Graphical abstract: Highlights: Membrane scaffold protein is used to form nanodisc and has diverse biotechnological applications. MSPs purified by Ni-NTA chromatography have abnormally high levels of endotoxin. Conventional anion exchange chromatography was not effective for MSP purification. Endotoxins could be separated from MSP after partial unfolding of MSP by urea. The endotoxin-free MSPs and nanodiscs are suitable for in vivo studies. Abstract: Membrane scaffold protein (MSP) is a versatile protein that can be used to study diverse membrane proteins. MSP is strongly expressed in E. coli ; however, applications of MSP in in vivo studies remain limited because of contamination with large amounts of endotoxins. Endotoxins cannot be easily removed from MSP following standard purification protocols for His6-tagged proteins, washing with detergents, or Q-Sepharose anion exchange chromatography, regardless of whether the expression host is E. coli BL21(DE3) or ClearColi BL21(DE3). Furthermore, the concentrations of MSP-bound endotoxins were not reduced during nanodisc formation, such that the assembled nanodiscs still contained significant amounts of endotoxins. We hypothesized that the structural properties of MSP that are responsible for membrane scaffolding mediated the strong binding between MSP and the endotoxins. We showed that partial denaturation of MSP with 2 M urea effectively disrupted MSP-endotoxin interactions. MSP-bound endotoxins were successfully removed via Q-Sepharose chromatography following urea treatment. The combined treatment with urea and Q-Sepharose resulted in ∼80-fold reduction in the specific endotoxin level relative to that of conventional Ni-NTA chromatography combined with detergent treatment. The low endotoxin level of 2.0 EU/mg MSP obtained in this study makes it suitable for applications in animal studies.